- 118
- 0
This is a basic simplification, but I'm going to post this here because it becomes homogeneous, and I know [tex]v = \frac{y}{x}[/tex] but I don't see this simplification, I don't understand how it gets from this...
[tex]\frac{dy}{dx} = \frac{y-x}{y+x}[/tex]
To THIS:
[tex] = \frac{v-1}{v+1}[/tex] (I'm just only showing the RHS here)
If someone wouldn't mind explaining it, that would be great because I'm lost, unless this is a special rule.
[tex]\frac{dy}{dx} = \frac{y-x}{y+x}[/tex]
To THIS:
[tex] = \frac{v-1}{v+1}[/tex] (I'm just only showing the RHS here)
If someone wouldn't mind explaining it, that would be great because I'm lost, unless this is a special rule.